2021
DOI: 10.4018/jgim.20211101.oa7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reviews vs. Regular Consumer Reviews

Abstract: This study proposes and evaluates the effect of “mixed” comparative reviews on review value and compares the results with “separate” comparative and regular reviews. A total of 201 subjects have participated in the experiment conducted in this study. Results indicate that mixed comparative reviews in text format are perceived as less valuable than separate comparative reviews in text format. However, mixed comparative reviews in tabular format have more review value than those in text format and are perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, the arousal generated from reading the review content and star ratings received also positively affect review helpfulness. Sometimes, the presentation format of the reviews may also play a part in the review processing (Vali et al, 2021). Apart from applying CTML in this study, we find that although ELM and HSM theories are widely acknowledged in the related literature (see Table A1 in Appendix), they do not directly address how multimedia can influence the helpfulness of online reviews.…”
Section: Cognitive Theory Of Multimedia Learning Multimedia Reviews A...mentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, the arousal generated from reading the review content and star ratings received also positively affect review helpfulness. Sometimes, the presentation format of the reviews may also play a part in the review processing (Vali et al, 2021). Apart from applying CTML in this study, we find that although ELM and HSM theories are widely acknowledged in the related literature (see Table A1 in Appendix), they do not directly address how multimedia can influence the helpfulness of online reviews.…”
Section: Cognitive Theory Of Multimedia Learning Multimedia Reviews A...mentioning
confidence: 89%
“…For instance, Wang and Tong (2022) have studied online product reviews and have shown from their results that along with characteristics of the review text, the perceived product quality and product-unrelated information from review images would also influence product sales. In another study, Vali et al (2021) propose and evaluate the effect of mixed comparative reviews on review value. The authors compare the results with separate comparative and regular reviews.…”
Section: Cognitive Theory Of Multimedia Learning Multimedia Reviews A...mentioning
confidence: 99%
“…In other words, potential customers' purchasing decisions are somehow influenced by what previous customers have commented on, so studying online reviews may help to understand customers' purchasing behavior (Ashraf et al. 2020; Vali, Xu, & Yildirim, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous buyers may describe the product based on their use of the item, and in this way, provide other potential customers with helpful information to assist them in further confirming that the product may match their needs. In other words, potential customers' purchasing decisions are somehow influenced by what previous customers have commented on, so studying online reviews may help to understand customers' purchasing behavior (Ashraf et al 2020;Vali, Xu, & Yildirim, 2021).…”
Section: Introductionmentioning
confidence: 99%